An Exploratory Study on E-Commerce System in Banking Sector: Internal Auditor's Perception on Risk and Control Environment - Abdullah, Amalina (2001)
In the development of Electronic Commerce in Malaysia, the banking sectors have already prepared and implemented the Internet Banking, which also known as virtual banking transaction for customers. The biggest challenge in electronic commerce implementation is to overcome the issues of security control, customer identification and account verification for online transaction. Despite of the growth of internet banking, lack of adequate legal framework especially for auditors and lack of security control will hamper the continued progress of this evolutionary process. Therefore, this study has been conducted to examine the internal auditor's perception, in general, on the risks, auditing problems and security measurement concerning with e-commerce or the internet banking transaction. This is an exploratory study which was conducted on the 16 domestic banks in Malaysia, including commercial banks and finance banks. The sample was chosen by using the non probability sampling specifically on the judgment sampling. The specific location is the Klang Valley area in the state of Selangor. The data was collected through personal interview, a developed questionnaires and various sources of journals and publications. From the data analysis, all the respondents agreed that the two most important perceived risk by internal auditors are security risk for unauthorization and computer fraud. The downtime computer system and electronic payment systems were ranked as the two most common problem with auditing e-commerce. Relating to e-commerce implementation, the most important factor perceived on control measurement are security control and integrity control. This finding suggest that a better security improvement should be taken by the banks with a very tight IT security policy. The increase in security awareness especially in banking sector will minimize the potential fraud and losses and indirectly improve the customers trust and confidence in using the bank products.